Improving regional soil water-salt management by modeling soil freezing-thawing processes in a cold-arid irrigation district, upper Yellow River basin - Lvyang Xiong; Yao Jiang; Junyu Qi; Guanhua Huang (Journal of Hydrology: Regional Studies)
Study region: The Hetao Irrigation District (Hetao), a super-large cold-arid irrigation district located in the upper Yellow River basin, China. Study focus: For cold-arid irrigation districts, understanding soil freezing-thawing processes is important for the reasonable management of non-growing season irrigation to improve soil water-salt conditions. This study aims to conduct regional agro-hydrological modeling with considering soil freezing-thawing processes in Hetao. The SWAT-AG model was adopted and enhanced by introducing a physically-based soil temperature module. Using the enhanced SWAT-AG, the agro-hydrological processes in Hetao were simulated and predicted under both the current autumn irrigation scheme (CAIS) and some water-saving autumn irrigation scenarios (WAIS). New hydrological insights for the region: The results proved that the enhanced SWAT-AG model effectively described the agro-hydrological processes during the soil freezing-thawing period. The simulated results of CAIS indicated that autumn irrigation was efficient in replenishing soil water and controlling soil salinity. The predictions from WAIS indicated that soil water content decreased, soil salt content increased, and groundwater depth became deeper compared to those under CAIS. A 20 % reduction in the current autumn irrigation amount did not compromise the effectiveness of autumn irrigation on soil water-salt and groundwater conditions, making it an appropriate autumn irrigation scheme for achieving both soil water-salt management and water saving in Hetao.